Resilience as a quadripartite responsibility: Indigenous students and distance education - Julie Anne Willems (Flexible Learning Association of New Zealand, 2012)
Considerations of educational resilience are often linked to student participation, retention, and outcomes in distance higher education, in spite of adversity, equity issues, or 'invisible fences' that students may face. This paper further develops the quadripartite model of educational resilience (Willems, 2010; Willems & Reupert, forthcoming); that is, educational resilience as the shared responsibility of students, educators, institutions, and communities-as a means to help assess and promote educational resilience and minimise student attrition in a specific cohort of distance learners, namely indigenous peoples. Through this lens the experiences of an online indigenous distance learner are explored.